Strategi Manajemen Risiko dalam Berwirausaha di Usia Muda - Alven Shendy Edu P; Djulis Azahra; Refan Fadilah (Jurnal Ekonomi dan Bisnis Digital, 2026)
This community service initiative aims to implement a risk management strategy framework within the context of youth entrepreneurship. The activity focuses on equipping participants with systematic knowledge and partical skills regarding the identification, analysis, evaluation, and formulation of business uncertainty commonly encountered by novice entrepreneurs. Through a participatory, educational, and applicative learning approach, participants are expected to develop the capacity to anticipate, manage, and mitigate the negative impacts of business riks from the planning stage. Evaluation results of the activity indicate a significant improvement in participants’ conceptual understanding of risk management principles, their ability to identify specific risks relevant to their competence in designing contextual and effective mitigation strategies. This initiative provides a substantive contribution to forming a risk-prepared mindset and developing entrepreneurial character that is mature, structured, and oriented towards long-term sustainability. More broadly, this activity is expected to encourage the emergence of a generation of young entrepremeurs who are more resilient, adaptive to change, and capable of contributing positively to strengthening the local and national economic ecosystem.